2003
DOI: 10.1016/s0002-9378(03)00852-4
|View full text |Cite
|
Sign up to set email alerts
|

High intraepithelial expression of estrogen and progesterone receptors in the transformation zone of the uterine cervix

Abstract: OBJECTIVE: Because sex hormones may be involved in tumor initiation and progression, we analyzed the presence of hormone receptors in the transformation zone of the uterine cervix where the majority of human papillomavirus infections and associated (pre)neoplastic lesions develop. STUDY DESIGN: By using 23 total hysterectomy samples from young women who underwent surgery for noncervical benign uterine disease, we analyzed, by immunohistologic techniques, the in situ expression of estrogen (E 2 -R) and progeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…[20][21][22] Nonetheless, it has long been recognized that cervical squamous epithelial cells contain sex-steroid receptors and hence, their proliferation and differentiation are influenced, to some extent, by the menstrual cycle and/ or sex-steroid hormonal levels. [20][21][22][23][24][25][26][27][28] Most studies have localized ERs and progesterone receptors (PRs), at minimum, to the basal and parabasal cell layers of the normal ectocervix. [20][21][22][23][24][25][26][27][28] Data on a possible correlation between the localization and the extent of ERs and the menstrual cycle phase are less homogeneous.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22] Nonetheless, it has long been recognized that cervical squamous epithelial cells contain sex-steroid receptors and hence, their proliferation and differentiation are influenced, to some extent, by the menstrual cycle and/ or sex-steroid hormonal levels. [20][21][22][23][24][25][26][27][28] Most studies have localized ERs and progesterone receptors (PRs), at minimum, to the basal and parabasal cell layers of the normal ectocervix. [20][21][22][23][24][25][26][27][28] Data on a possible correlation between the localization and the extent of ERs and the menstrual cycle phase are less homogeneous.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28] Most studies have localized ERs and progesterone receptors (PRs), at minimum, to the basal and parabasal cell layers of the normal ectocervix. [20][21][22][23][24][25][26][27][28] Data on a possible correlation between the localization and the extent of ERs and the menstrual cycle phase are less homogeneous. Kanai et al 23 and Ciocca et al 22 both reported that the expression and localization of steroid hormone receptors did not vary significantly with the phase of the menstrual cycle.…”
mentioning
confidence: 99%
“…Using K14-HPV16 transgenic mice in which the expression of HPV16 E6 and E7 oncogenes is driven by the keratin 14 promoter in the basal keratinocytes of the squamous epithelium, some investigators have shown that the TZ is five-fold more sensitive to the induction of squamous cell carcinogenesis by estrogen compared to other sites of the reproductive tract (Elson et al, 2000). We also found, by using immunohistological techniques and total hysterectomy samples from young women undergoing surgery for non-cervical benign uterine disease, that TZ biopsies with immature squamous metaplasia exhibit a significantly higher density of hormone receptor-positive cells compared to ectocervical epithelium, suggesting that the TZ may be at increased risk of developing (pre)neoplastic lesions because of a high sensitivity to sex hormone regulation (Remoue et al, 2003). Although endometrial expression of estrogen and progesterone receptors has been shown to vary during the menstrual cycle (Fujishita et al, 1997;Ravn et al, 1994), no significant difference was demonstrated in hormone receptor-positive cell density between the follicular and luteal phases in both TZ and ectocervical biopsies (Remoue et al, 2003).…”
Section: Role Of Sex Hormones In the Induction Of Squamous Metaplasiamentioning
confidence: 70%
“…We also found, by using immunohistological techniques and total hysterectomy samples from young women undergoing surgery for non-cervical benign uterine disease, that TZ biopsies with immature squamous metaplasia exhibit a significantly higher density of hormone receptor-positive cells compared to ectocervical epithelium, suggesting that the TZ may be at increased risk of developing (pre)neoplastic lesions because of a high sensitivity to sex hormone regulation (Remoue et al, 2003). Although endometrial expression of estrogen and progesterone receptors has been shown to vary during the menstrual cycle (Fujishita et al, 1997;Ravn et al, 1994), no significant difference was demonstrated in hormone receptor-positive cell density between the follicular and luteal phases in both TZ and ectocervical biopsies (Remoue et al, 2003). These data are in agreement with previous studies showing no significant variation, within the menstrual cycle, in hormone receptor concentrations in vaginal tissues (Schwartz, 2000) and in HPV-associated lesions (Monsonego et al, 1991), suggesting a lower sensitivity to menstrual cycle changes of genital squamous mucosa compared to glandular endometrial tissues.…”
Section: Role Of Sex Hormones In the Induction Of Squamous Metaplasiamentioning
confidence: 70%
“…Transformation zone epithelium is more susceptible to human papillomavirus (HPV) infection and estrogen-induced squamous metaplasia that can lead to cervical carcinoma (Elson et al, 2000). High levels of ER and PR are expressed in transformation zone epithelium in humans (Remoue et al, 2003). Both ERa and PR are expressed throughout the sea lion cervix and vagina surrounding these epithelial transition zones, and similar to dogs, there was little variation in receptor expression in the cervix and vagina throughout the cycle (Vermeirsch et al, 2002).…”
Section: Estrogen and Progesterone Receptor Expressionmentioning
confidence: 95%